If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 6 = 21 Reorder the terms: 6 + 5y = 21 Solving 6 + 5y = 21 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5y = 21 + -6 Combine like terms: 6 + -6 = 0 0 + 5y = 21 + -6 5y = 21 + -6 Combine like terms: 21 + -6 = 15 5y = 15 Divide each side by '5'. y = 3 Simplifying y = 3
| -23+7x-5X=17 | | 3(t-12)=27 | | -6-3(2k+4)=18 | | -4x+3(2x-5)=31 | | 2(m+1)=16 | | 4x+20=x+50 | | 4(2a+2)-17=15 | | 11x=3+8x | | 5(3x+12)=-15 | | 9-6x=3x | | 13+2(5c-2)=29 | | (3x+10)=(5x+2) | | 5x-14=16+3x | | 2y+4=10 | | x+20=35 | | 3r-6=2r | | 3x+8=16x-4 | | (3y+11)+10y=180 | | c+3(5+c)=28 | | (7x+4)+(4x-22)=180 | | 4(4x-2)=56 | | 5y=(7y-34) | | 20+15x=10x+30 | | 4(-4-6x)=-28x+20 | | 10x-2=5x+8 | | 3+2x-1=7x+10-4x | | -9x+6(7x)=378-9 | | 7R-8=19-2R | | 9+5x=-5x+79 | | 8(6x+18)=288 | | 8(6x+18)=18x | | 6(6+8x)=78+42x |